Strategy for Strengthening Fiscal Independence Thru Optimization of Regional Original Revenue (PAD): A Study on Lebak Regency, Banten Province - Rusito Rusito; Jumanah Jumanah (INFOKUM, 2026)
This study aims to analyze strategies for strengthening fiscal independence through the optimization of Local Own-Source Revenue (PAD) in Lebak Regency, Banten Province. The research employs a descriptive qualitative approach supported by quantitative data obtained through observation, in-depth interviews, and documentation studies. The analysis focuses on the main dimensions within the framework of fiscal decentralization (Fiscal Federalism), namely revenue assignment, expenditure assignment, intergovernmental transfers, and fiscal accountability and efficiency in regional financial management. The results indicate that the level of fiscal independence in Lebak Regency remains relatively low, as the regional revenue structure is still dominated by transfers from the central government. The contribution of Local Own-Source Revenue (PAD) to total regional revenue remains limited compared to intergovernmental transfers such as the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH). This condition suggests that the capacity of the regional government to optimize local revenue sources needs to be strengthened through improving the effectiveness of local tax and retribution collection, productive management of regional assets, and the development of local economic potentials such as tourism, agriculture, and micro, small, and medium enterprises (MSMEs). Therefore, the optimization of PAD becomes an important strategy to enhance regional fiscal capacity, reduce dependence on central government transfers, and support sustainable regional development financing in Lebak Regency.